THE IMPACT OF HELMINTH DISEASE: A LITERATURE REVIEW - Muslim, Nurhadi; Hasyim, Hamzah; Nurrobikha, Nurrobikha; Nurhasanah, Nurhasanah; Sari, Nining Indah; Lestari, Ocik; Sari, Nurmaya; Sigalingging, Nurhaida (LPPM Universitas Prima Nusantara Bukittinggi, 2021)
According to the World Health Organization (WHO), over 1.5 billion individuals, or roughly 24% of the global population, are infected with intestinal worms, which primarily affect school-aged children. India is home to a third of the world's 2.5 billion people without access to proper sanitation, as well as two-thirds of the 11 billion people who practice open defecation and a quarter of the 15 million people who die each year from diarrhoeal diseases. This work does a literature review to investigate the effects of helminthiasis. The articles obtained were extracted and conclusions were drawn from a literature study of intestinal worms using the PubMed database; the number of articles extracted became a conclusion of up to 30 articles, and the strategy for searching for articles in the database used the keywords